2009
DOI: 10.1002/path.2493
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anti‐tumour immunity by dendritic cells transduced with hTERT recombinant adenovirus in mice

Abstract: Dendritic cells (DCs) transfected with recombinant, replication-defective adenovirus (Ad) vectors encoding the human telomerase reverse transcriptase (hTERT) are potent inducers of cytotoxic T lymphocytes (CTLs) and anti-tumour immunity. However, previous studies have mostly been in vitro. In this study, we sought to determine whether DCs transfected with hTERT (DC/Ad-hTERT) could elicit a potent anti-tumour immunogenic response in vivo. We found that murine DCs transfected with recombinant adenovirus encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…16 Furthermore, the transduction of dendritic cells with recombinant-adenovirus hTERT induced hTERT-specific cytotoxic T lymphocytes in vitro and in vivo . 17, 18 During a previous study, we showed that hTERT promoted the invasion of telomerase-negative tumor cells in vitro . 19 Moreover, we also demonstrated that hTERT RNAi overcame the resistance of HCC cells to TRAIL via the mitochondrial type II apoptosis pathway and a telomerase-dependent pathway.…”
Section: Discussionmentioning
confidence: 98%
“…16 Furthermore, the transduction of dendritic cells with recombinant-adenovirus hTERT induced hTERT-specific cytotoxic T lymphocytes in vitro and in vivo . 17, 18 During a previous study, we showed that hTERT promoted the invasion of telomerase-negative tumor cells in vitro . 19 Moreover, we also demonstrated that hTERT RNAi overcame the resistance of HCC cells to TRAIL via the mitochondrial type II apoptosis pathway and a telomerase-dependent pathway.…”
Section: Discussionmentioning
confidence: 98%
“…However, heterogeneous expression of most of the characterized tumor antigens limits the broad applicability of cancer vaccines that target such antigens (25,26). Therefore, it is necessary for clinicians to identify universal TAAs for immunotherapy of different types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Because RNA-based vaccines have many advantages including easily preparation, low price, specificity, control, and no risk of incorporation into the host genome [61]. DCs were transfected with tumor mRNA encoding TAA or epitopes by using carriers [61, 62] or electroporation [63, 64]. This can also induce tumor-specific immunity in vitro .…”
Section: Methods Used In Genetically Engineered Dcsmentioning
confidence: 99%